Evaluation of Chlamydia trachomatis Genotypes in Endocervical Specimens by Sequence Analysis of ompA Gene among Women in Tehran - Mohammadreza Rajabpour; Amir Darb Emamie; Mohammad Reza Pourmand (Journal of Tropical Medicine)
Tehran’s actual prevalence of Chlamydia trachomatis (CT) and its genotypes are still unclear. Molecular typing of CT strains can provide essential epidemiological knowledge and contribute to improved control measures. In this study, we aimed to determine the prevalence of CT and its genotypes in the endocervical infections of females who attended the gynecology and infertility clinics in Tehran. A total of 291 women were tested for chlamydial infection by in-house PCR using specific primers for the CT cryptic plasmid. Nested PCR for amplification of the ompA gene in positive samples was carried out, genotyping was performed by sequencing this gene, and further phylogenetic analysis was conducted. Sexual infection by CT was observed in 10.3% (30/291) of the subjects, and the mean age of patients was 30.4. The ompA gene was sequenced in 27 samples, revealing E genotypes 40.7%, (n = 11), F 25.9%, (n = 7), G 18.5%, (n = 5), D 11.1%, (n = 3), and K 3.7%, (n = 1). This study emphasizes the importance of the diversity among CT genotypes in our studied population and the need for wide-screening the neglected bacterial infection among women in Tehran.